DETERMINAN PERILAKU RUMAH TANGGA DALAM PENGHEMATAN ENERGI LISTRIK DI WILAYAH JAWA BARAT MENGGUNAKAN STRUCTURAL EQUATION MODELING - Siti Sadiah; Fitria Virgantari; Ani Andriyani; Sri Hartini; Dion Achmad (Universitas Pakuan, 2020)
This study aims to analyze the Theory Planned of Behavior model using Structural Equation Modeling and analyze the factors that influence household behavior in electricity consumption in West Java. The data used in this study are secondary data on electricity consumption in lighting equipment obtained from the Renewable Energy and Energy Conservation database in 2016. The results showed that behavioral intention and control had a positive and significant effect on behavior, then behavior control had a positive and significant effect. significant on intention. While subjective attitudes and norms do not significantly influence intention. The indicators that influence a person's behavior factors in saving electrical energy in lighting equipment are individual self-awareness to use household appliances that are labeled energy efficient, lifestyle of individuals who often fill their time for cooking activities at home, gathering with friends and family, visiting market, stamp collection, and individuals who work as volunteers, participate in community activities, and gardening.